Burden of dengue infection in India, 2017: a cross-sectional population based serosurvey. Issue 8 (August 2019) - Murhekar, Manoj V; Kamaraj, P; Kumar, Muthusamy Santhosh; Khan, Siraj Ahmed; Allam, Ramesh Reddy; Barde, Pradip; Dwibedi, Bhagirathi; Kanungo, Suman; Mohan, Uday; Mohanty, Suman Sundar; Roy, Subarna; Sagar, Vivek; et al.
Summary: Background: The burden of dengue virus (DENV) infection across geographical regions of India is poorly quantified. We estimated the age-specific seroprevalence, force of infection, and number of infections in India. Methods: We did a community-based survey in 240 clusters (118 rural, 122 urban), selected from 60 districts of 15 Indian states from five geographical regions. We enumerated each cluster, randomly selected (with an Andriod application developed specifically for the survey) 25 individuals from age groups of 5–8 years, 9–17 years, and 18–45 years, and sampled a minimum of 11 individuals from each age group (all the 25 randomly selected individuals in each age group were visited in their houses and individuals who consented for the survey were included in the study). Age was the only inclusion criterion; for the purpose of enumeration, individuals residing in the household for more than 6 months were included. Sera were tested centrally by a laboratory team of scientific and technical staff for IgG antibodies against the DENV with the use of indirect ELISA. We calculated age group specific seroprevalence and constructed catalytic models to estimate force of infection. Findings: From June 19, 2017, to April 12, 2018, we randomly selected 17 930 individuals from three age groups. Of these, blood samples were collected and tested for 12 300 individuals (5–8 years, n=4059; 9–17 years, n=4265; 18–45 years, n=3976). The overall seroprevalence of DENV infection in India was 48·7% (95% CI 43·5–54·0), increasing from 28·3% (21·5–36·2) among children aged 5–8 years to 41·0% (32·4–50·1) among children aged 9–17 years and 56·2% (49·0–63·1) among individuals aged between 18–45 years. The seroprevalence was high in the southern (76·9% [69·1–83·2]), western (62·3% [55·3–68·8]), and northern (60·3% [49·3–70·5]) regions. The estimated number of primary DENV infections with the constant force of infection model was 12 991 357 (12 825 128–13 130 258) and for the age-dependent force of infection model was 8 655 425 (7 243 630–9 545 052) among individuals aged 5–45 years from 30 Indian states in 2017. Interpretation: The burden of dengue infection in India was heterogeneous, with evidence of high transmission in northern, western, and southern regions. The survey findings will be useful in making informed decisions about introduction of upcoming dengue vaccines in India. Funding: Indian Council of Medical Research.